Light Activated Bleaching of Discoloured Non-Vital Tooth: A Case Report - Sahithi Reddy1 , Alagarsamy Venkatesh2 , Newbegin Selvakumar Gold Pearlin Mary3 , Paramasivam Viveka (Institute of Medico-legal Publications Pvt Ltd, 2020)
Trauma and pulpal infections are part of the routine of the dental practice. Common consequences inthese cases are alterations in dental color, compromising patient’s esthetics and his interaction in socialenvironment. Bleaching aids to preserve dental structure as compared to full coverage crowns and alsoshow immediate esthetic results. This clinical case shows a bleaching technique in devitalized teeth usingbleaching agent with 35% hydrogen peroxide activated by LED light. The technique is simple to performand also shows satisfactory results.